Criminalization of Social Protest: future research - Terwindt, Carolijn (Oñati Socio-Legal Series, 2014)
This special issue of the Oñati Socio-Legal Series is dedicated to an exploration of particular features of and analytical approaches to the criminalization of social protest about natural resources. This epilogue highlights four areas for future research: (1) the definition and use of the term ‘criminalization of social protest’ and the development of an analytical apparatus; (2) patterns, typologies, and legal strategies of criminalization; (3) the embeddedness of processes of criminalization in the broader political decision-making procedures about natural resources; (4) counter-strategies. In the description of these areas, the author draws on the papers in this Special Issue and the collective reflection during the workshop in 2012.